Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(B=3^2+3^3+...+3^{99}\)
\(3B=3^3+3^4+...+3^{100}\)
\(3B-B=\left(3^3+3^4+...+3^{100}\right)-\left(3^2+3^3+...+3^{99}\right)\)
\(2B=3^{100}-3^2\)
\(B=\frac{3^{100}-9}{2}\)
\(2B+9=3^{2n+4}\)
\(\Leftrightarrow3^{2n+4}=3^{100}\)
\(\Leftrightarrow2n+4=100\)
\(\Leftrightarrow n=48\).
a)
x-3 | 1 | -1 | 7 | -7 |
2y +1 | 7 | -7 | 1 | -1 |
x | 4 | 2 | 10 | -4 |
y | 3 | -4 | 0 | -1 |
b)
2x +1 | 1 | -1 | 5 | -5 | 11 | -11 | 55 | -55 |
3y-2 | -55 | 55 | -11 | 11 | -5 | 5 | -1 | 1 |
x | 0 | -1 | 2 | -3 | 5 | -6 | 27 | -28 |
y | / | 19 | -3 | / | -1 | / | / | 1 |
Có 4 đáp số :(x =-1; y =19) ; (x =2 ; y =-3)
(x =5 ; y =-1) ; (x =-28 ; y =1)
a,(x-3)(2y+1)=7
Ta co: 7=1.7=7.1=(-1).(-7)=(-7).(-1)
\(\Rightarrow\)(x-3)(2y+1)=1.7 hay (x-3)(2y+1)=7.1 hay (x-3)(2y+1)=(-1).(-7) hay (x-3)(2y+1)=(-7).(-1)
TH1: \(\text{(x-3)(2y+1)=}1.7\Rightarrow\orbr{\begin{cases}\left(x-3\right)=1\\\left(2y+1\right)=7\end{cases}\Rightarrow\orbr{\begin{cases}x=4\\y=3\end{cases}}\left(TM\right)}\)
TH2: \(\text{(x-3)(2y+1)=7.1}\Rightarrow\orbr{\begin{cases}\text{(x-3)=7}\\\text{ }\text{(2y+1)=1}\end{cases}\Rightarrow\orbr{\begin{cases}x=10\\y=0\end{cases}}\left(TM\right)}\)
TH3:\(\text{(x-3)(2y+1)=(-1).(-7)}\Rightarrow\orbr{\begin{cases}\text{(x-3)=-1}\\\text{(2y+1)=-7}\end{cases}\Rightarrow\orbr{\begin{cases}x=4\\y=-8\end{cases}\left(TM\right)}}\)
TH4: \(\text{(x-3)(2y+1)=(-7).(-1)}\Rightarrow\orbr{\begin{cases}\text{(x-3)=-7}\\\text{(2y+1)=-1}\end{cases}\Rightarrow\orbr{\begin{cases}x=-4\\y=-1\end{cases}\left(TM\right)}}\)
Vay (x,y)={(4,3);(10,0);(4,-8);(-4;-1)}
b, (2x+1)(3y-2)=-55
Ta co: -55=-1.55=1.(-55)=55.(-1)=-55.1=-11.5=11.(-5)=5.(-11)=-5.11
\(\Rightarrow\)(2x+1)(3y-2)=-1.55 hay (2x+1)(3y-2)=1.(-55) hay (2x+1)(3y-2)=55.(-1) hay (2x+1)(3y-2)=-55.1 hay (2x+1)(3y-2)=-11.5
hay (2x+1)(3y-2)=11.(-5) hay (2x+1)(3y-2)=5.(-11) hay (2x+1)(3y-2)=-5.11
TH1:\(\text{(2x+1)(3y-2)=-1.55}\Rightarrow\orbr{\begin{cases}\text{(2x+1)=-1}\\\text{(3y-2)=55}\end{cases}\Rightarrow\orbr{\begin{cases}x=-1\\y=19\end{cases}\left(TM\right)}}\)
TH2:\(\text{(2x+1)(3y-2)=1.(-55)}\Rightarrow\orbr{\begin{cases}\text{(2x+1)=1}\\\text{(3y-2)=-55}\end{cases}\Rightarrow\orbr{\begin{cases}x=0\\y=\frac{-53}{3}\end{cases}\Rightarrow}\left(loai\right)}\)
TH3:\(\text{(2x+1)(3y-2)=55.(-1)}\Rightarrow\orbr{\begin{cases}\text{(2x+1)=55}\\\text{(3y-2)=-1}\end{cases}\Rightarrow\orbr{\begin{cases}x=27\\y=\frac{1}{3}\end{cases}\left(loai\right)}}\)
TH4: \(\text{(2x+1)(3y-2)=-55.1}\Rightarrow\orbr{\begin{cases}\text{(2x+1)=-55}\\\text{(3y-2)=1}\end{cases}\Rightarrow\orbr{\begin{cases}x=-28\\y=1\end{cases}\left(TM\right)}}\)
TH5: \(\text{(2x+1)(3y-2)=-11.5}\Rightarrow\orbr{\begin{cases}\text{(2x+1)=-11}\\\text{(3y-2)=5}\end{cases}\Rightarrow\orbr{\begin{cases}x=-6\\y=\frac{7}{3}\end{cases}\left(loai\right)}}\)
TH6: \(\text{(2x+1)(3y-2)=11.(-5)}\Rightarrow\orbr{\begin{cases}\text{(2x+1)=11}\\\text{(3y-2)=-5}\end{cases}\Rightarrow\orbr{\begin{cases}x=5\\y=-1\end{cases}\left(TM\right)}}\)
TH7:\(\text{(2x+1)(3y-2)=5.(-11)}\Rightarrow\orbr{\begin{cases}\text{(2x+1)=5}\\\text{(3y-2)=-11}\end{cases}\Rightarrow\orbr{\begin{cases}x=4\\y=-3\end{cases}\left(TM\right)}}\)
TH8:\(\text{(2x+1)(3y-2)=-5.11}\Rightarrow\orbr{\begin{cases}\text{(2x+1)=-5}\\\text{(3y-2)=11}\end{cases}\Rightarrow\orbr{\begin{cases}x=-3\\y=\frac{13}{3}\end{cases}\left(loai\right)}}\)
â) Ta có : \(2n-1⋮n+1\Leftrightarrow2n+2-2-1⋮n+1\)
\(\Leftrightarrow2\left(n+1\right)-2-1⋮n+1\)\(\Leftrightarrow2\left(n+1\right)-3⋮n+1\)
\(\Leftrightarrow2n-1⋮n+1\)khi \(3⋮n+1\Rightarrow n+1\in\)Ước của \(3\) \
\(\Leftrightarrow n+1\in\left(1;-1;3;-3\right)\)
\(\Leftrightarrow n\in\left(0;-2;2;-4\right)\)
Vậy \(n\in\left(-4;-2;0;2\right)\)
b) Ta có :\(9n+5⋮3n-2\Rightarrow3\left(3n-2\right)+6+5⋮3n-2\)
\(\Rightarrow3\left(3n-2\right)+11⋮3n-2\)
\(\Rightarrow9n+5⋮3n-2\)Khi \(11⋮3n-2\)
\(\Rightarrow3n-2\in U\left(11\right)\)
\(\Rightarrow3n-2\in\left(-11;-1;1;11\right)\)
\(\Rightarrow n\in\left(-3;1;\right)\)
Phần c) bạn tự làm nhé!
M = 182018 + 20162017
= (2.9)2018 + (9.224)2017
= 92018.22018 + 92017.2242017
= 92017(9.22018 + 2242017) \(⋮\)9 (1)
Lại có : M = 182018 + 20162017
= 182016.182 + (...6)2017
= (184)504.(...4) + (...6)
= (....6)504.(...4) + (...6)
= (...6).(...4) + (...6) = (...4) + (...6) = (...0) \(⋮5\)(2)
lại có (9;5) = 1 (3)
Từ (1)(2)(3) => M \(⋮\)9.5= 45
a; -2024 + 1094 + 2024 + (-1094) + 103
=(-2024 + 2024) + (1094 - 1094) + 103
= 0 + 0 + 103
= 103
b; 347 + 844 + (-347) + (-844) + 1
= [347 + (-347)] + [844 + (-844)] + 1
= 0 + 0 + 1
= 1
c; 2017 + (-2018) + 2018 + (-2017) + 5010
= [2017 + (-2017)] + [(-2018) + 2018] + 5010
= 0 + 0 + 5010
= 5010
a) \(-2024+1094+2024+\left(-1094\right)+103\)
\(=[-2024+2024]+[1094+\left(-1094\right)]+103\)
\(=103\)
b) \(347+844+\left(-347\right)+\left(-844\right)+1\)
\(=[347+\left(-347\right)]+[844+\left(-844\right)]+1\)
\(=1\)
c) \(2017+\left(-2018\right)+2018+\left(-2017\right)+5010\)
\(=[2017+\left(-2017\right)]+[\left(-2018\right)+2018]+5010\)
\(=5010\)